2020
DOI: 10.1016/j.hpb.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic grade 3 neuroendocrine tumors behave similarly to neuroendocrine carcinomas following resection: a multi-center, international appraisal of the WHO 2010 and WHO 2017 staging schema for pancreatic neuroendocrine lesions

Abstract: Background: In 2017, the WHO updated their 2010 classification of pancreatic neuroendocrine tumors, introducing a well-differentiated, highly proliferative grade 3 tumor, distinct from neuroendocrine carcinomas. The aim of this study was to investigate the clinical significance of this update in a large cohort of resected tumors. Methods: Using a multicenter, international dataset of patients with pancreatic neuroendocrine lesions, patients were classified both according to the WHO 2010 and 2017 schema. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…A recent study of 28 patients operated with pancreatic NEN G−3 showed that NET G−3 have similar postoperative survival compared to NEC, which was significantly lower than for NET G−2 and G−1 [47]. Both localized and metastatic tumors were evaluated in this work, so it is hard to conclude [47]. As mentioned above, we can also speculate that NEC surgical trials probably evaluated some misdiagnosed NET G−3 [33,[43][44][45].…”
Section: Surgery and Liver-targeted Therapiesmentioning
confidence: 81%
See 2 more Smart Citations
“…A recent study of 28 patients operated with pancreatic NEN G−3 showed that NET G−3 have similar postoperative survival compared to NEC, which was significantly lower than for NET G−2 and G−1 [47]. Both localized and metastatic tumors were evaluated in this work, so it is hard to conclude [47]. As mentioned above, we can also speculate that NEC surgical trials probably evaluated some misdiagnosed NET G−3 [33,[43][44][45].…”
Section: Surgery and Liver-targeted Therapiesmentioning
confidence: 81%
“…Nevertheless, surgery is still debated in localized NEC because of the high risk of metastatic relapse and the absence of prospective clinical trials; so neoadjuvant chemotherapy and chemoradiation can also be considered, especially when surgical resection is difficult or at risk [37,46]. A recent study of 28 patients operated with pancreatic NEN G−3 showed that NET G−3 have similar postoperative survival compared to NEC, which was significantly lower than for NET G−2 and G−1 [47]. Both localized and metastatic tumors were evaluated in this work, so it is hard to conclude [47].…”
Section: Surgery and Liver-targeted Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Worth et al 1 reported that patients with resected G3 neuroendocrine tumors (NET) and neuroendocrine carcinomas (NEC) may have similar postoperative survival, a finding contradictory with current knowledge. [2][3][4] Of note, this study included only 15 patients with G3 NET and 13 with NEC.…”
mentioning
confidence: 85%
“…One study on 28 patients operated for PanNEN G-3 suggested that patients with NET G-3 have similar postoperative survival compared to those with NEC, which was significantly lower than for NET G-2 and G-1 patients [ 81 ]. This is contradictory with current knowledge on NET G-3 prognosis and these results could be explained by the pooled evaluation of both localized and metastatic tumors [ 3 , 26 , 67 , 82 ].…”
Section: Treatmentmentioning
confidence: 99%